ANALISIS TEKANAN PORI BAWAH PAnalysis of subsurface pore pressure is used to determine the potential problems that can occur in formation. The research purpose to determine sERMUKAAN MENGGUNAKAN METODE EATON PADA SUMUR ELNUSA BERDASARKAN DATA WELL LOGGING - Datu, Bonaria; Djayus, Djayus; Natalisanto, Adrianus Inu (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
Analysis of subsurface pore pressure is used to determine the potential problems that can occur in formation. The research purpose to determine subsurface pressure using the Eaton method and identify potential drilling problems, so prevention can be done to reduce accidents. Research on BD 325 wells is secondary data in the form of resistivity and density log data. Analysis of subsurface pressure is carried out using the Eaton method which results in normal pore pressure and pressure values. Based on the results of graph analysis, the pore pressure value shows the depth interval 3943.9 ft – 3949.1 ft pressure average 5.4 ppg, depth 4407.8 ft - 4417.6 ft pressure average 0.6 ppg, depth 4546.9 ft - 4554.8 ft pressure average 1.4 ppg, depth 4748.3 ft – 4753 ft pressure average 4.8 ppg and depth 5026.5 ft - 5033.7 ft pressure average 4.7 ppg where 5 zones experience subnormal pressure, so it can be concluded that the potential problems can occur lost circulation because the hydrostatic pressure of the mud is greater than the formation pressure which results in loss of drilling mud entering the formation.